Multi-element Polychromatic 2-dimensional Liquid Crystal Dammann Gratings - Zhao, Z; Chen, B; Salter, P S; Booth, M J; O'Brien, D; Elston, S J; Morris, S M (University of Oxford, 2022)
This is the underlying data from the publication: Zimo Zhao, Bohan Chen, Patrick S. Salter, Martin J. Booth, Dominic O’Brien, Steve J. Elston, and Stephen M. Morris, "Multi-element Polychromatic 2-dimensional Liquid Crystal Dammann Gratings"